Cultural Literacy in Indonesian Language Learning for Foreign Speakers (BIPA): Overcoming Barriers and Fostering Language Proficiency with Cross-Cultural Understanding Issues - Tiawati, Refa Lina; Kurnia, Maya Dewi; Nazriani, Nazriani; Annisa, Witri; Harahap, Safinatul Hasanah (Journal of Pragmatics and Discourse Research, 2024)
This study explores the main challenges in teaching Indonesian language (BIPA) in international classrooms, particularly addressing the limited knowledge of Indonesian culture that learners encounter in BIPA. Another significant challenge is the constraint of materials and teaching strategies related to Indonesian culture, especially regional cultures, which may have an impact on BIPA instruction in Indonesia. The primary goal is to enhance the use of the Indonesian language among foreign learners through cross-cultural understanding and a cognitive approach that supports its implementation. This research also aims to identify the impact of community practices on language learning, believing that interaction within this community enhances students' language abilities. Using a linguistic phenomenology design, this study involves direct classroom observations supported by field notes, providing insights into interactions and teaching practices. Semi-structured interviews with instructors contribute to a deeper understanding of perspectives and challenges in teaching BIPA, particularly concerning cross-cultural understanding in its instruction. Findings indicate that not all BIPA instructors utilize cultural materials and strategies in teaching. However, with high levels of student knowledge about Minangkabau culture, such as food, art, clothing, and traditional houses observed in West Sumatra, gaps in their learning arise. Time management issues emerge as a significant concern affecting the effectiveness of teaching cross-cultural understanding in foreign language instruction. This research provides valuable insights for enhancing BIPA instruction in international classrooms, emphasizing the importance of understanding community practices in cross-cultural understanding in BIPA instruction.